2010
DOI: 10.1111/j.1467-8543.2009.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the Life Course Savings Scheme Have the Potential to Improve Work–Life Balance?

Abstract: To improve individuals' work-life balance, trade unions, employers' organizations, governments and the European Commission currently promote a life course perspective in activating labour market policies. In 2006, the Life Course Savings Scheme (Levensloopregeling) was introduced in the Netherlands, which aims to increase labour participation and to improve the work-life balance over the life course. What can we learn from the Dutch case? In 2006, actual participation in the scheme was with 6% much lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…As a consequence, higher rather than lower income groups, employees with assets rather than employees without, men rather than women, and full timers rather than part timers, and older rather than younger employees, have the financial scope to benefit from this scheme (Kösters 2007; see also Den Dulk and van Doorne Huiskes 2008). A more recent study showed that the higher participation rates of some of these groups were related to the higher earnings (Delsen and Smits 2010). After controlling for earnings, the participation turns out to be higher among females, part timers and the young.…”
Section: How Do Employees Use Leave Saving Options? Some Evidence From the Netherlandsmentioning
confidence: 95%
See 2 more Smart Citations
“…As a consequence, higher rather than lower income groups, employees with assets rather than employees without, men rather than women, and full timers rather than part timers, and older rather than younger employees, have the financial scope to benefit from this scheme (Kösters 2007; see also Den Dulk and van Doorne Huiskes 2008). A more recent study showed that the higher participation rates of some of these groups were related to the higher earnings (Delsen and Smits 2010). After controlling for earnings, the participation turns out to be higher among females, part timers and the young.…”
Section: How Do Employees Use Leave Saving Options? Some Evidence From the Netherlandsmentioning
confidence: 95%
“…Regarding the 'transitional' approach, many researchers and policymakers have repeatedly stressed the importance and potential of options for accumulating longer periods of leave (see e.g. Anxo and Boulin 2006: 331;BMFSFJ 2006;Delsen and Smits 2010;European Foundation 2012a: 5). Countries in which such options exist are Denmark, Germany, Sweden, Finland, France and (until January 2012) the Netherlands (Anxo and Boulin 2006;European Foundation 2012b).…”
Section: New Models To Combinementioning
confidence: 99%
See 1 more Smart Citation
“…The Netherlands introduced a scheme of life-saving accounts in 2006 that permits workers to deposit up to 12 per cent of their salary tax-free into an account to be used at a later date to finance additional periods of unpaid, parental or study leave. In this way it is hoped that individuals will be able to modulate their working time better so as ‘to ease the combination of work and other activities over the life-cycle’ (Delsen and Smits 2010: 584).…”
Section: De-commodificaton and The Concept Of Wlbmentioning
confidence: 99%
“…30 See, for instance, Delsen/ Smits (2009), Roman (2006, Wotschack/ Hildebrandt (2008). 31 Another reason for the discrepancy between 'nominal' and 'effective' employment rate could be institutional.…”
Section: Policy Debatementioning
confidence: 99%